Effect of Growth Factor In Callus Induction and Bioactive Compounds In Seed Explant of Kaffir Lime (Citrus hystrix DC.) - Tunjung, Woro Anindito Sri; Fatonah, Vita; Christy, Ghea Putri; Triono, Sugeng; Hidayati, Lisna (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2020)
Our previous study showed that kaffir lime leaf extracts may have anti-cancer properties. However, production of bioactive compounds is affected by environmental factors. Here, we present a method to control environmental conditions using in vitro culture techniques such as callus induction. Calluses were induced from seed embryo explants of kaffir lime on MS medium with combinations of 2,4-D and BAP at concentrations 1:0.5; 1:1; and 2:1, respectively. Fourty and 60 days-old calluses were extracted using chloroform and ethyl acetate and analyzed by GC-MS. Results showed all combinations of 2,4-D and BAP were able to induce callogenesis from seed embryo explants of kaffir lime with no significant differences of callus initiation time, biomass, morphology and growth rates. However differences were detected in the bioactive compound profiles. In kaffir lime callus, both fatty acids and secondary metabolites were detected. Specifically, in 40 days-old calluses (exponential growth phase) we detected α-pinene and 1.8–cineole in plants treated with 2,4-D: BAP at concentration 1:0.5 and 2:1. In 60 days-old calluses (stationary phase) we detected a number of compounds in plants treated with 2,4-D:BAP at concentrations of 1:0.5 and 2:1, including caryophyllene, linoleoyl chloride, thiogeraniol, stigmasterol, clianosterol, citronellal, neo-isopulegol, citronellol, geraniol, eugenol, cyclopropane, pristane, elemol and farnesol